2022
DOI: 10.3389/fimmu.2022.873985
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CXCR3+ CD8+ T-Lymphocyte Subsets in Peripheral Blood Is Associated With the Risk of Paradoxical Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome Development in Advanced HIV Disease

Abstract: BackgroundTuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is a clinical aggravation of TB symptoms observed among a fraction of HIV coinfected patients shortly after the start of antiretroviral therapy (ART). Of note, TB-IRIS is characterized by exacerbated inflammation and tissue damage that occurs in response to the elevated production of CD4+ T cell-derived IFN-γ. Nevertheless, the possible participation of CD8+ T cells in TB-IRIS development remains unclear.MethodsWe performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…A recent study from India revealed increased frequencies of antigen-experienced CD8 + T cells among TB-IRIS patients correlating with the AFB smear gradings. The study also demonstrates an inverse association between IRIS and naïve CXCR3 + CD8 + T cells substantiating the role of CD8 + T cells in TB-IRIS [ 103 ].…”
Section: Immunopathogenesis Of Paradoxical Tb-irissupporting
confidence: 62%
“…A recent study from India revealed increased frequencies of antigen-experienced CD8 + T cells among TB-IRIS patients correlating with the AFB smear gradings. The study also demonstrates an inverse association between IRIS and naïve CXCR3 + CD8 + T cells substantiating the role of CD8 + T cells in TB-IRIS [ 103 ].…”
Section: Immunopathogenesis Of Paradoxical Tb-irissupporting
confidence: 62%